18th International Symposium on Medical Information Processing and Analysis 2023
DOI: 10.1117/12.2670093
|View full text |Cite
|
Sign up to set email alerts
|

Assessing coarse-to-fine deep learning models for optic disc and cup segmentation in fundus images

Abstract: Automated optic disc (OD) and optic cup (OC) segmentation in fundus images is relevant to efficiently measure the vertical cup-to-disc ratio (vCDR), a biomarker commonly used in ophthalmology to determine the degree of glaucomatous optic neuropathy. In general this is solved using coarse-to-fine deep learning algorithms in which a first stage approximates the OD and a second one uses a crop of this area to predict OD/OC masks. While this approach is widely applied in the literature, there are no studies analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…This model outperforms most advanced algorithms available for disc and cup segmentation tasks. Moris et al (2023) , Guo et al (2019) conducted a comprehensive analysis of different coarse-to-fine designs of optic disc/OC segmentation from the perspective of standard segmentation and vCDR for evaluating glaucoma. The analysis showed that when these methods learn from particularly large and diverse training sets, they do not outperform the standard multiclass single-level models ( Guo et al, 2019 ).…”
Section: Related Workmentioning
confidence: 99%
“…This model outperforms most advanced algorithms available for disc and cup segmentation tasks. Moris et al (2023) , Guo et al (2019) conducted a comprehensive analysis of different coarse-to-fine designs of optic disc/OC segmentation from the perspective of standard segmentation and vCDR for evaluating glaucoma. The analysis showed that when these methods learn from particularly large and diverse training sets, they do not outperform the standard multiclass single-level models ( Guo et al, 2019 ).…”
Section: Related Workmentioning
confidence: 99%